EVALUASI PROGRAM PENYELENGGARAAN MADRASAH ALIYAH NEGERI (MAN) MODEL TERNATE - ADAM NURDIN; YULIATRI SASTRAWIJAYA (Jurnal Evaluasi Pendidikan, 2012)
This study is an evaluative study with reference to the evaluation model CIPPO with a focus on the evaluation context, input, process, product, and outcome. The purpose of this study is to determine the effectiveness of MAN Model Ternate. The research was conducted in 2011 at the MAN Model Ternate. Subjects in the study include students, teachers, head of the madrasah, superintendent of education, and parents/committee madrasah. Data collected through observation, interviews, documentation analysis, and questionnaires. Data analysis technique used to interpret the descriptive data analysis of data from every aspect that was evaluated, then compared with predefined criteria. The results of evaluation show that there were aspects in the context of MAN Model Ternate considered quite good, including the legality of the implementation of MAN Model and the presence of much needed community programs. In the aspect of input, facilities and infrastructure has been very adequate, 100% have qualified teachers and teaching appropriate undergraduate disciplines, curriculum development has been in accordance with the content standard, and standards of graduted competency (SKL). The management of madrasah was good, only on students and poor community participation, where only 20% of learners who gain the admission criteria as well as community participation is still low. In the aspect of the process, the ability of teachers to teach, the activities of teachers and students in learning is good, just supervision from supervisors who lack good education. In aspects of the product, already very well where the graduation of students has reached 100%. In the aspect shown that the overall outcome does not gain the criteria, where only 41% of graduates are absorbed in college and 4,35% of graduates are received in the world of work.